The influence of intellectual intelligence, emotional intelligence, and spiritual intelligence on social adjustment - Sururi, Robitotus; Sudarjon, Sudarjon; Kholilah, Kholilah; Ismail, Iriani (International Journal Labs, 2023)
Social adjustment is a person's ability to interact with their social environment. Intellectual, emotional, and spiritual intelligence are considered to have an influence on a person's social adjustment. This study aims to identify and analyze the influence of intellectual, emotional, and spiritual intelligence on social adjustment. The method used in this research is a literature study by collecting data from various sources such as books, journals, and related articles. The results of this study indicate that intellectual, emotional, and spiritual intelligence have a positive influence on social adjustment. Intellectual intelligence can help a person in understanding and dealing with social problems, emotional intelligence can help a person in controlling emotions and interacting with others effectively, and spiritual intelligence can help a person in finding the meaning and purpose of life that can motivate to be positive in interacting with their social environment.